NILAI-NILAI PENDIDIKAN ISLAM DALAM TRADISI GUSJIGANG SUNAN KUDUS: REFLEKSI DAN IMPLEMENTASI - Zahro, Shella Sayidatuz; Haq, Ubaidil; Serli, S; Arif, Ahmad Miftahul; Kusno, Moh. (Al’ulum Jurnal Pendidikan Islam, 2025)
This study examines the Islamic educational values in the Gusjigang life philosophy inherited from Sunan Kudus and its implementation in contemporary Islamic education. Gusjigang is an acronym for Gus (having good morals), Ji (intelligent in knowledge), and Gang (economically independent), shaping individuals and societies that are civilized, knowledgeable, and economically self-sufficient.  Using a qualitative approach with a literature study method, this research analyzes various sources related to Gusjigang and Islamic education. Content analysis identifies six key values: philosophical (honesty and justice), moral (discipline and responsibility), scientific (lifelong learning), spiritual (connection with God), creative (creativity and innovation), and economic (Islamic business ethics and financial independence). The findings show that Gusjigang values are highly relevant in Islamic education and can be implemented through curriculum integration, project-based learning, as well as character and entrepreneurship education based on Islamic principles. Adapting the Gusjigang philosophy in the education system is expected to nurture Muslim generations who are morally upright, knowledgeable, and economically independent while preserving Islamic values and local culture.